The BLASST Report : Benchmarking Leadership and Advancement of Standards for Sessional Teaching : Final Report. - Harvey, Marina (Office for Learning and Teaching, 2014)
This is the final report from the Benchmarking Leadership and Advancement of Standards for Sessional Teaching (BLASST) project, which established evidence-based national standards to support and enhance quality learning and teaching by sessional staff. These standards were informed by seminal national and internal project outcomes and recommendations. The project established five key objectives and achieved outcomes for each. These included: development of national standards to support and enhance quality learning and teaching by sessional staff (the BLASST framework, to be endorsed by TEQSA); an on-line interactive to facilitate the self-assessment benchmarking process with the capability of generating a customised report and action plan (the BLASST B-BIT); an implementation guide on how to use the sessional staff standards framework and self-assessment tool (the BLASST guide); a leadership summit for national dissemination of the sessional staff standards framework (the BLASST national summit), and; a refereed publication (comprising of eight of the national summit papers) as a special issue of the online, open-access Journal of University Teaching and Learning Practice, Volume 10, Issue 3.